Community of Communities: Jews in Mexico - Dayan, Renne; Roitman, Deborah (Cuadernos Judaicos, 2016)
Jewish immigrants who arrived in Mexico during the first half of the 20th century, formed communities according to their places of origin, a lifestyle that persists to this day. They formed a highly organized and cohesive community, under a high rank of well-being, that includes religious, educational, cultural services and more. Likewise, in there more than 100 years of life they have achieved a high attendance of their children to the Jewish school network and a low index of exogamous marriages, avoiding the assimilation. Today its members are considered highly integrated to the Mexican society, which are a part. This article is of descriptive order, where it tries to expose the Mexican Jewish community, covering diverse areas that constitute it.